Pengaruh Nilai Inti AKHLAK dalam Kerangka Levers of Control terhadap Kecenderungan Kecurangan Akuntansi - Aldila Yanri (Universitas Serang Raya, 2024)
This research investigates the relationship between AKHLAK core values in the framework of levers of control and accounting fraud within PT Pelabuhan Indonesia (Persero) or Pelindo. The research design was conducted using primary data in the form of a 5-point Likert scale questionnaire, with purposive sampling technique. The data collected came from 69 respondents from a total of 80 samples. Data quality and classical assumption tests were conducted before the data were further analyzed using multiple linear regression analysis. The results showed that AKHLAK core values have a negative and significant effect on the tendency of accounting fraud. In addition, the levers of control framework proved to be able to moderate the negative effect of AKHLAK core values on the tendency of accounting fraud.